The erythrocyte sedimentation rate time curve: critique of an established solution. - Dorrington, K; Johnston, B (1983)
A sigmoid curve is required to characterize the time course of the erythrocyte sedimentation rate (ESR) test. The widely used 'logistic' form has been thought to have a theoretical foundation in a sedimentation model of Puccini et al. (1977) which claims to account for the sigmoid form without rouleaux formation. We show the curve of these authors to result from a mathematical error in their analysis, and reaffirm the need to accommodate cell aggregation in models of the ESR.